High-strength corrosion-resistant aluminum alloy brazing plate for power battery water cooling plate and preparation method of high-strength corrosion-resistant aluminum alloy brazing plate

By using high-strength corrosion-resistant aluminum alloy brazed plates and using the composite structure of the brazing layer and the core layer, the existing water-cooled plates are solved, and high strength and good corrosion resistance are achieved.

CN119663063AActive Publication Date: 2025-03-21NORTHEAST LIGHT ALLOY CO LTD

Patent Information

Application Number
CN202411772330.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-21
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing water-cooled plate made of 3003 aluminum alloy is difficult to meet the user's needs due to insufficient strength and corrosion resistance.

Method used

A high-strength corrosion-resistant aluminum alloy brazed sheet composed of a rolling composite brazed aluminum alloy is made of a brazing layer and a core material layer. The aluminum alloy content of the core material layer is 0.4% to 1.0%, Si, 0.2% to 0.7%, Fe, 0.2% to 1.1% Cu, 1.2% to 1.8% Mn, Zn≤0.05%, Ti is 0.05% to 0.2%, and the balance is Al; the brazing layer is 4045 aluminum alloy.

Benefits of technology

The high strength and good corrosion resistance of the plate were achieved. The average grain size of the core material was ≤80μm, the yield strength ≥60MPa, the tensile strength ≥160MPa, the yield strength after brazing was ≥55MPa, the tensile strength ≥150MPa, and the corrosion depth after 50 days of soaking was about 75μm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663063A_ABST
    Figure CN119663063A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength corrosion-resistant aluminum alloy brazing plate for a power battery water-cooling plate and a preparation method of the high-strength corrosion-resistant aluminum alloy brazing plate, and aims to solve the problem that an existing water-cooling plate made of 3003 aluminum alloy is limited by strength and corrosion resistance. And the use requirements of users are difficult to meet. The high-strength corrosion-resistant aluminum alloy brazing plate is made of a composite plate, the composite plate is formed by rolling and compounding a core material layer and a brazing layer, and the core material layer is composed of Si, Fe, Cu, M, Zn, Ti and Al. The preparation process comprises the steps of fusion casting, homogenization treatment, ingot casting treatment, brazing layer preparation, material covering, preheating before rolling, hot rolling, cold rolling, finished product annealing, finishing and shearing. The high-strength corrosion-resistant aluminum alloy brazing plate is high in strength, good in ductility, not prone to cracking after being formed, high in strength after brazing and excellent in corrosion resistance. The water-cooling plate is applied to the field of power battery water-cooling plates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-strength corrosion-resistant aluminum alloy brazing plate for a power battery water-cooling plate and a preparation method thereof. Background Art

[0002] With the rapid development of the automobile industry, the problems of environmental pollution, reduced oil reserves, and resource depletion caused by traditional fuel vehicles are becoming increasingly serious, which is contrary to the national carbon peak and carbon neutrality policies. Through structural changes, new energy vehicles can use a variety of clean energy for power drive, have good environmental performance, and are conducive to improving the shortage of traditional energy. In 2023, the production capacity of major new energy vehicle OEMs will continue to increase, and the production and sales of new energy vehicles will reach 9.587 million and 9.495 million respectively, a year-on-year increase of 35.8% and 37.9%, with a market share of 31.6%.

[0003] As the core component of the power system of new energy vehicles, the temperature change during the use of the power battery has a great impact on its safety. When the temperature is too high, the battery is prone to thermal runaway, so the establishment of a battery thermal management system is crucial. The water-cooling plate is an important component in the battery thermal management system. The surface of the water-cooling plate is in full contact with the surface of the battery cell. It uses ethylene glycol and water as cooling media. Relying on the high specific heat capacity and excellent thermal conductivity of the mixed liquid, it takes away the heat generated by the battery during operation to keep the battery working within a suitable temperature range.

[0004] In the early stage, the water cooling plates of new energy vehicles were welded with 3003 aluminum alloy plates. However, as power batteries develop towards long battery life and ultra-fast charging, higher requirements are placed on the performance of power battery water cooling plates, including mechanical properties and corrosion resistance. Water cooling plates made of ordinary 3003 aluminum alloy are difficult to meet the needs of users due to their strength limitations. Summary of the invention

[0005] In order to solve the problem that the existing water-cooling plate made of 3003 aluminum alloy is limited by strength and corrosion resistance and is difficult to meet the user's usage requirements, the present invention provides a high-strength and corrosion-resistant aluminum alloy brazing plate for a power battery water-cooling plate and a preparation method thereof.

[0006] The invention discloses a high-strength corrosion-resistant aluminum alloy brazing sheet for a power battery water-cooling plate, which is formed by rolling and compounding a brazing layer and a core material layer. The core material layer aluminum alloy consists of 0.4% to 1.0% Si, 0.2% to 0.7% Fe, 0.2% to 1.1% Cu, 1.2% to 1.8% Mn, Zn≤0.05%, Ti of 0.05% to 0.2%, and the balance Al in terms of mass percentage; the brazing layer is 4045 aluminum alloy.

[0007] A method for preparing a high-strength and corrosion-resistant aluminum alloy brazing sheet for a power battery water-cooling plate is carried out in the following steps:

[0008] 1. According to the mass percentage, weigh 0.4% to 1.0% Si, 0.2% to 0.7% Fe, 0.2% to 1.1% Cu,

[0009] 1.2% to 1.8% Mn, Zn≤0.05%, Ti is 0.05% to 0.2%, and the balance is Al, to obtain the raw material of the core material layer; then semi-continuous casting is performed to obtain the core material layer alloy ingot;

[0010] 2. heating the core alloy ingot to 600°C to 630°C and keeping it at that temperature for 16h to 24h to perform homogenization annealing treatment on the ingot;

[0011] 3. Milling the brazing layer 4045 alloy ingot and the core material layer alloy ingot processed in step 2;

[0012] 4. hot rolling and sawing the preheated brazing layer alloy ingot;

[0013] 5. stacking the hot-rolled brazing layer alloy ingot on the core material layer alloy ingot, and punching holes in the direction perpendicular to the plate surface at the four corners of the brazing layer blank plate and the core material layer alloy ingot and riveting them together to obtain a composite alloy ingot;

[0014] 6. Preheating the composite alloy ingot, and then hot rolling it to form a composite hot-rolled coil; rolling the composite hot-rolled coil again to form a composite cold-rolled coil, and annealing it to obtain an annealed coil;

[0015] 7. The annealed coil is straightened, shaped and sheared on a stretch-bending straightening machine to obtain a high-strength, corrosion-resistant aluminum alloy brazing sheet for a power battery water-cooling plate.

[0016] Beneficial effects of the present invention:

[0017] The brazing sheet of the present invention has good mechanical properties, is suitable for stamping and forming, and has good corrosion resistance. According to performance testing, the average grain size of the core material of the high-strength and corrosion-resistant aluminum alloy brazing sheet for power battery water-cooling plate is ≤80μm, the yield strength of the finished composite plate is ≥60MPa, the tensile strength is ≥160MPa, the elongation is ≥24%, the yield strength after brazing is ≥55MPa, the tensile strength is ≥150MPa, and the corrosion depth after immersion for 50 days after brazing is about 75μm. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Process flow chart for preparing high-strength and corrosion-resistant aluminum alloy brazing sheet for this application;

[0019] Figure 2The metallographic structure diagram of the high-strength and corrosion-resistant aluminum alloy brazing plate prepared in Example 3 of the present application;

[0020] Figure 3 This is the metallographic structure diagram of the high-strength and corrosion-resistant aluminum alloy plate after brazing prepared in Example 3 of the present application. DETAILED DESCRIPTION

[0021] Specific implementation method 1: In this implementation method, a high-strength and corrosion-resistant aluminum alloy brazing plate for a power battery water-cooling plate is formed by rolling and compounding a brazing layer and a core material layer. The core material layer aluminum alloy is composed of 0.4% to 1.0% Si, 0.2% to 0.7% Fe, 0.2% to 1.1% Cu, 1.2% to 1.8% Mn, Zn≤0.05%, Ti is 0.05% to 0.2%, and the remainder is Al in terms of mass percentage; the brazing layer is 4045 aluminum alloy.

[0022] By adopting the proportion of this embodiment, the melting amount of the solder can meet the brazing requirements without causing the core material to be eroded due to excessive solder.

[0023] The Mn content of the core material of the water-cooled plate in this embodiment is 1.2% to 1.8%. The high Mn content can strengthen the alloy and increase the recrystallization temperature of the plate. The increase in the Mn content can further reduce the diffusion of other solute atoms and improve the heat resistance and strength of the alloy. When the Mn content is lower than 0.5%, the strengthening effect on the alloy is insufficient, but when the Mn content is greater than 1.8%, the solid solubility of Mn in the alloy reaches the limit, and it is easy to precipitate from the matrix and form a large amount of Al6Mn brittle compounds, which are easy to cause cracking during deformation. In order to improve the strength of the composite plate, the Mn content of this application is preferably not less than 1.2%.

[0024] The core material Fe of the water-cooled plate in this embodiment can dissolve in Al6Mn to form Al6(FeMn) compounds. The appropriate amount of Al6(FeMn) phase can avoid the accumulation of aluminum chips in the mold during the stamping process of the plate. If the Fe content is higher than 0.7%, a large amount of coarse Al6(FeMn) compounds will be formed, which will significantly reduce the mechanical properties of the alloy. In this application, the Fe content is controlled at 0.2% to 0.7%.

[0025] The core material Si of the water-cooled plate of this embodiment can form a complex T phase (Al 12 Mn3Si2), and Si can also promote the decomposition of the supersaturated solid solution to form high-density dispersed fine particles, thereby improving the strength of the alloy. When the Si content is higher than 0.9%, the melting point of the core alloy decreases, increasing the risk of core corrosion during brazing. In this application, the Si content is controlled below 1.0%.

[0026] The core material Cu of the water-cooled plate in this embodiment can cause lattice distortion of the α solid solution in the alloy, enrich in the dislocation-intensive area, hinder dislocation slip, and strengthen the alloy. When the Cu content exceeds 0.1%, an Al2Cu phase can be formed, which can also improve the strength of the alloy. Cu can also increase the corrosion potential of the alloy and increase the corrosion resistance of the core material alloy. However, the Cu content should not be too high, otherwise it will deteriorate the intergranular corrosion resistance of the alloy and reduce the corrosion resistance of the alloy. The Cu content in this application does not exceed 1.0%.

[0027] Adding Ti to the core alloy of the water-cooled plate in this embodiment can refine the cast grains, prevent cracking during alloy casting, and improve the corrosion resistance of the alloy to a certain extent. However, when the Ti content is greater than 0.15%, a coarse Al3Ti phase may be formed in the ingot, which may easily cause cracks and lead to cracking of the ingot. In this application, the Ti content is controlled between 0.05% and 0.2%.

[0028] Specific implementation method 2: In this implementation method, a method for preparing a high-strength and corrosion-resistant aluminum alloy brazing sheet for a power battery water-cooling plate is carried out according to the following steps:

[0029] 1. Weigh 0.4% to 1.0% Si, 0.2% to 0.7% Fe, 0.2% to 1.1% Cu, 1.2% to 1.8% Mn, Zn≤0.05%, Ti is 0.05% to 0.2%, and the balance is Al according to the mass percentage to obtain the raw material of the core material layer; then perform semi-continuous casting to obtain the alloy ingot of the core material layer;

[0030] 2. heating the core alloy ingot to 600°C to 630°C and keeping it at that temperature for 16h to 24h to perform homogenization annealing treatment on the ingot;

[0031] 3. Milling the brazing layer 4045 alloy ingot and the core material layer alloy ingot processed in step 2;

[0032] 4. hot rolling and sawing the preheated brazing layer alloy ingot;

[0033] 5. stacking the hot-rolled brazing layer alloy ingot on the core material layer alloy ingot, and punching holes in the direction perpendicular to the plate surface at the four corners of the brazing layer blank plate and the core material layer alloy ingot and riveting them together to obtain a composite alloy ingot;

[0034] 6. Preheating the composite alloy ingot, and then hot rolling it to form a composite hot-rolled coil; rolling the composite hot-rolled coil again to form a composite cold-rolled coil, and annealing it to obtain an annealed coil;

[0035] 7. The annealed coil is straightened, shaped and sheared on a stretch-bending straightening machine to obtain a high-strength, corrosion-resistant aluminum alloy brazing sheet for a power battery water-cooling plate.

[0036] Specific implementation method 3: This implementation method is different from specific implementation method 2 in that the thickness of the brazing layer alloy ingot is 5% to 10% of the thickness of the alloy ingot after compounding. Other aspects are the same as specific implementation method 2.

[0037] Specific implementation method 4: This implementation method is different from specific implementation method 2 or 3 in that the milling process in step 3 is as follows: the milling depth of the upper and lower surfaces is 5mm to 15mm, and the milling depth of the small surfaces on both sides is 2mm to 10mm. The rest is the same as specific implementation method 2 or 3.

[0038] Specific embodiment 5: This embodiment differs from specific embodiments 2 to 4 in that: Step 4 is to place the brazing layer alloy ingot in a heating furnace and preheat it to 480°C to 520°C for 2h to 6h to obtain the preheated brazing layer alloy ingot. The rest is the same as specific embodiments 2 to 4.

[0039] Specific embodiment 6: This embodiment is different from specific embodiments 2 to 5 in that in step 6, the composite ingot is preheated to 460° C. to 500° C. and kept warm for 2 h to 4 h. The rest is the same as specific embodiments 2 to 5.

[0040] Specific embodiment 7: This embodiment is different from specific embodiments 2 to 6 in that the starting rolling temperature of step 6 hot rolling is 420° C. to 480° C., and the final rolling temperature is 300° C. to 360° C. The rest is the same as specific embodiments 2 to 6.

[0041] Specific embodiment 8: This embodiment differs from specific embodiments 2 to 7 in that the thickness of the composite hot-rolled material billet in step 6 is 3.0 mm to 5.0 mm. The rest is the same as specific embodiments 2 to 7.

[0042] Specific embodiment 9: This embodiment is different from specific embodiments 2 to 8 in that the reduction rate of the final rolling pass of the composite cold rolled coil is 20% to 40%, and the finished product thickness is 1.0 mm to 2.0 mm. Other aspects are the same as specific embodiments 2 to 8.

[0043] Specific embodiment 10: This embodiment differs from specific embodiments 2 to 9 in that the annealing temperature in step 6 is 340° C. to 440° C. and the heat preservation time is 1 h to 3 h. The rest is the same as specific embodiments 2 to 9.

[0044] The content of the present invention is not limited to the content of the above-mentioned embodiments. The combination of one or several specific embodiments can also achieve the purpose of the invention.

[0045] The present application is described in detail below with reference to specific embodiments:

[0046] Example 1

[0047] The mass percentage of the core material components are as follows: Si: 0.7%, Fe: 0.5%, Cu: 1.0%, Mn: 1.7%, Zn: 0.05%, Ti: 0.16%, the individual content of the impurity elements is <0.05%, the total amount is <0.15%, and the balance is Al.

[0048] (1) Melting and Casting: Raw materials are weighed according to the above-mentioned components and added into a melting furnace for melting. After melting, electromagnetic stirring, slag removal, degassing, refining, and semi-continuous casting, a core material layer alloy ingot is obtained; the brazing layer alloy ingot is a 4045 alloy ingot with a specification of 440 mm × 1600 mm × 4900 mm, and the core material layer alloy ingot has a specification of 440 mm × 1700 mm × 4900 mm.

[0049] (2) Homogenization treatment: After the core alloy is cast, the ingot is heated to 620°C and kept warm for 20 hours for homogenization annealing to reduce and eliminate intracrystalline segregation.

[0050] (3) Ingot processing: The brazing layer ingot and the core material layer ingot are milled according to the specification requirements. The milling depth of the upper and lower surfaces is 10 mm, and the milling depth of the small surfaces on both sides is 5 mm. The head and tail parts of the ingot are cut off.

[0051] (4) Preparation of brazing layer: The brazing layer alloy ingot was placed in a heating furnace and preheated to 500°C for 3 h. It was then hot rolled into a slab with a thickness of 40 mm and then sawn into 40 mm × 1600 mm × 4000 mm.

[0052] (5) Material cladding: The brazing layer blank plate is stacked on the core material layer alloy ingot, and holes are punched at the four corners of the brazing layer blank plate and the core material layer alloy ingot in a direction perpendicular to the plate surface and riveted.

[0053] (6) Preheating before rolling: The mechanically compounded alloy ingot is preheated to 500°C and kept warm for 2 hours.

[0054] (7) Hot rolling: The preheated composite ingot is hot rolled at a starting rolling temperature of 480°C and a final rolling temperature of 320°C, and rolled into a 4.0 mm composite hot rolled coil in multiple passes.

[0055] (8) Cold rolling: The composite hot rolled coil is rolled into a 1.5 mm composite cold rolled coil through three passes, and the final rolling processing rate is 25%.

[0056] (9) Finished product annealing: The composite cold-rolled coil is subjected to finished product annealing at a temperature of 400°C for 2 hours.

[0057] (10) Finishing: The finished annealed coil is straightened and shaped on a stretch-bend straightening machine to obtain a finished aluminum alloy composite sheet.

[0058] (11) Shearing: The finished aluminum alloy composite sheet is sheared and formed to obtain a high-strength and corrosion-resistant aluminum alloy finished sheet for a power battery water cooling plate.

[0059] (12) Simulated brazing: The finished composite panels were placed in a Nabertherm test furnace for simulated brazing at a simulated brazing temperature of 610 °C for 5 min. The panels were slowly cooled to 300 °C in the furnace and then air-cooled to room temperature.

[0060] The average grain size of the core material of the composite plate is 66.0μm. According to GB / T 16865-2023 "Test specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products", the longitudinal tensile strength of the high-strength and corrosion-resistant aluminum alloy brazing sheet for power battery water cooling plate prepared in this application is 173.3MPa, the yield strength is 65.0MPa, and the elongation after fracture is 24.0%. The tensile strength of the composite plate after brazing is 168.2MPa and the yield strength is 59.6MPa. According to GB / T7998-2023 standard, the brazed composite plate is subjected to an immersion corrosion test, and the corrosion depth of the plate is 80μm after 50 days of immersion.

[0061] Example 2

[0062] The weight percentage of the core material components is as follows: Si: 0.6%, Fe: 0.4%, Cu: 0.6%, Mn: 1.6%, Zn: 0.03%, Ti: 0.15%, the individual content of the impurity elements is less than 0.05%, the total amount is less than 0.15%, and the balance is Al.

[0063] (1) Melting and Casting: Raw materials are weighed according to the above-mentioned components and added into a melting furnace for melting. After melting, electromagnetic stirring, slag removal, degassing, refining, and semi-continuous casting, a core material layer alloy ingot is obtained; the brazing layer alloy ingot is a 4045 alloy ingot with a specification of 440 mm × 1600 mm × 4900 mm, and the core material layer alloy ingot has a specification of 440 mm × 1700 mm × 4900 mm.

[0064] (2) Homogenization treatment: After the core alloy is cast, the ingot is heated to 610°C and kept warm for 20 hours for homogenization annealing to reduce and eliminate intracrystalline segregation.

[0065] (3) Ingot processing: The brazing layer ingot and the core material layer ingot are milled according to the specification requirements. The milling depth of the upper and lower surfaces is 10 mm, and the milling depth of the small surfaces on both sides is 5 mm. The head and tail parts of the ingot are cut off.

[0066] (4) Preparation of brazing layer: The brazing layer alloy ingot was placed in a heating furnace and preheated to 510°C for 2 h. It was then hot rolled into a slab with a thickness of 40 mm and then sawn into 40 mm × 1600 mm × 4000 mm.

[0067] (5) Material cladding: The brazing layer blank plate is stacked on the core material layer alloy ingot, and holes are punched at the four corners of the brazing layer blank plate and the core material layer alloy ingot in a direction perpendicular to the plate surface and riveted.

[0068] (6) Preheating before rolling: The mechanically compounded alloy ingot is preheated to 490°C and kept warm for 3 hours.

[0069] (7) Hot rolling: The preheated composite ingot is hot rolled at a starting rolling temperature of 470°C and a final rolling temperature of 320°C, and rolled into a 4.0 mm composite hot rolled coil in multiple passes.

[0070] (8) Cold rolling: The composite hot rolled coil is rolled into a 2.0 mm composite cold rolled coil through three passes, and the final rolling processing rate is 29%.

[0071] (9) Finished product annealing: The composite cold-rolled coil is subjected to finished product annealing at a temperature of 420°C for 1.5 hours.

[0072] (10) Finishing: The finished annealed coil is straightened and shaped on a stretch-bend straightening machine to obtain a finished aluminum alloy composite sheet.

[0073] (11) Shearing: The finished aluminum alloy composite plate is sheared and formed to obtain a high-strength and corrosion-resistant aluminum alloy brazing plate for a power battery water cooling plate.

[0074] (12) Simulated brazing: The finished composite panels were sampled and placed in a Nabertherm test furnace for simulated brazing. The simulated brazing temperature was 600 °C and the temperature was kept at that temperature for 6 min. The panels were slowly cooled to 350 °C in the furnace and then air-cooled to room temperature.

[0075] The average grain size of the core material of the composite plate is 70.5μm. According to GB / T 16865-2023 "Test specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products", the longitudinal tensile strength of the high-strength and corrosion-resistant aluminum alloy brazing sheet for power battery water cooling plate prepared in this application is 171.0MPa, the yield strength is 64.2MPa, and the elongation after fracture is 25.1%. The tensile strength of the composite plate after brazing is 165.5MPa and the yield strength is 58.4MPa. According to GB / T7998-2023 standard, the brazed composite plate is subjected to an immersion corrosion test, and the corrosion depth of the plate after 50 days of immersion is 75μm.

[0076] Example 3

[0077] The weight percentage of the core material components is as follows: Si: 0.7%, Fe: 0.5%, Cu: 0.7%, Mn: 1.5%, Zn: 0.05%, Ti: 0.14%, the individual content of the impurity elements is <0.05%, the total amount is <0.15%, and the balance is Al.

[0078] (1) Melting and Casting: Raw materials are weighed according to the above-mentioned components and added into a melting furnace for melting. After melting, electromagnetic stirring, slag removal, degassing, refining, and semi-continuous casting, a core material layer alloy ingot is obtained; the brazing layer alloy ingot is a 4045 alloy ingot with a specification of 440 mm × 1600 mm × 4900 mm, and the core material layer alloy ingot has a specification of 440 mm × 1700 mm × 4900 mm.

[0079] (2) Homogenization treatment: After the core alloy is cast, the ingot is heated to 610°C and kept warm for 18 hours for homogenization annealing to reduce and eliminate intracrystalline segregation.

[0080] (3) Ingot processing: The brazing layer ingot and the core material layer ingot are milled according to the specification requirements. The milling depth of the upper and lower surfaces is 10 mm, and the milling depth of the small surfaces on both sides is 5 mm. The head and tail parts of the ingot are cut off.

[0081] (4) Preparation of brazing layer: The brazing layer alloy ingot is placed in a heating furnace and preheated to 500°C for 2 hours. It is then hot rolled into a slab with a thickness of 40 mm and then sawn into 40 mm × 1600 mm × 4000 mm.

[0082] (5) Material cladding: The brazing layer blank plate is stacked on the core material layer alloy ingot, and holes are punched at the four corners of the brazing layer blank plate and the core material layer alloy ingot in a direction perpendicular to the plate surface and riveted.

[0083] (6) Preheating before rolling: The mechanically compounded alloy ingot is preheated to 500°C and kept warm for 2 hours.

[0084] (7) Hot rolling: The preheated composite ingot is hot rolled at a starting rolling temperature of 480°C and a final rolling temperature of 320°C, and rolled into a 4.0 mm composite hot rolled coil in multiple passes.

[0085] (8) Cold rolling: The composite hot rolled coil is rolled into a 1.0 mm composite cold rolled coil through three passes, and the final rolling processing rate is 33%.

[0086] (9) Finished product annealing: The composite cold-rolled coil is subjected to finished product annealing at a temperature of 400°C for 2 hours.

[0087] (10) Finishing: The finished annealed coil is straightened and shaped on a stretch-bend straightening machine to obtain a finished aluminum alloy composite sheet.

[0088] (11) Shearing: The finished aluminum alloy composite sheet is sheared and formed to obtain a high-strength and corrosion-resistant aluminum alloy brazing sheet for a power battery water cooling plate.

[0089] (12) Simulated brazing: The finished composite panels were sampled and placed into a Nabertherm test furnace for simulated brazing. The simulated brazing temperature was 590 °C and the temperature was kept at that temperature for 8 min. The panels were slowly cooled to 300 °C in the furnace and then air-cooled to room temperature.

[0090] The average grain size of the core material of the composite plate is 73.0μm. According to GB / T 16865-2023 "Test specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products", the longitudinal tensile strength of the high-strength and corrosion-resistant aluminum alloy brazing sheet for power battery water cooling plate prepared in this application is 168.0MPa, the yield strength is 63.2MPa, and the elongation after fracture is 24.8%. The tensile strength of the composite plate after brazing is 161.3MPa and the yield strength is 59.2MPa. According to GB / T7998-2023 standard, the brazed composite plate is subjected to an immersion corrosion test, and the corrosion depth of the plate after 50 days of immersion is 72μm. Figure 1 The figure is a process flow chart of the preparation method of the above embodiment.

[0091] Figure 2 The figure shows the metallographic structure of the composite plate obtained in this embodiment. It can be seen that the brazing layer of the composite plate is evenly coated with a coating rate of 10%, the structure of the core layer is a recrystallized structure, the grains are evenly distributed, the long sides are distributed along the rolling direction, and the average grain size is 73.0μm.

[0092] Figure 3 The figure shows the metallographic structure of the composite plate after brazing obtained in this embodiment. It can be seen that the brazing layer of the composite plate recrystallizes and grows after melting, the brazing layer after welding is evenly distributed, the structure of the core material layer is a recrystallized structure, the grains grow after brazing, and the long sides are distributed along the rolling direction.

[0093] Example 4

[0094] The mass percentage of the core material components are as follows: Si: 0.5%, Fe: 0.35%, Cu: 0.5%, Mn: 1.5%, Zn: 0.04%, Ti: 0.13%, the individual content of the impurity elements is <0.05%, the total amount is <0.15%, and the balance is Al.

[0095] (1) Melting and Casting: Raw materials are weighed according to the above-mentioned components and added into a melting furnace for melting. After melting, electromagnetic stirring, slag removal, degassing, refining, and semi-continuous casting, a core material layer alloy ingot is obtained; the brazing layer alloy ingot is a 4045 alloy ingot with a specification of 440 mm × 1600 mm × 4900 mm, and the core material layer alloy ingot has a specification of 440 mm × 1700 mm × 4900 mm.

[0096] (2) Homogenization treatment: After the core alloy is cast, the ingot is heated to 600°C and kept warm for 20 hours for homogenization annealing to reduce and eliminate intracrystalline segregation.

[0097] (3) Ingot processing: The brazing layer ingot and the core material layer ingot are milled according to the specification requirements. The milling depth of the upper and lower surfaces is 10 mm, and the milling depth of the small surfaces on both sides is 5 mm. The head and tail parts of the ingot are cut off.

[0098] (4) Preparation of brazing layer: The brazing layer alloy ingot was placed in a heating furnace and preheated to 490°C for 3 h. It was then hot rolled into a slab with a thickness of 40 mm and then sawn into 40 mm × 1600 mm × 4000 mm.

[0099] (5) Material cladding: The brazing layer blank plate is stacked on the core material layer alloy ingot, and holes are punched at the four corners of the brazing layer blank plate and the core material layer alloy ingot in a direction perpendicular to the plate surface and riveted.

[0100] (6) Preheating before rolling: The mechanically compounded alloy ingot is preheated to 490°C and kept warm for 2 hours.

[0101] (7) Hot rolling: The preheated composite ingot is hot rolled at a starting rolling temperature of 470°C and a final rolling temperature of 320°C, and is rolled in multiple passes into a 4.2 mm composite hot rolled coil.

[0102] (8) Cold rolling: The composite hot rolled coil is rolled into a 1.5 mm composite cold rolled coil through three passes, and the final rolling processing rate is 25%.

[0103] (9) Finished product annealing: The composite cold-rolled coil is subjected to finished product annealing at a temperature of 380°C for 2 hours.

[0104] (10) Finishing: The finished annealed coil is straightened and shaped on a stretch-bend straightening machine to obtain a finished aluminum alloy composite sheet.

[0105] (11) Shearing: The finished aluminum alloy composite sheet is sheared and formed to obtain a high-strength and corrosion-resistant aluminum alloy brazing sheet for a power battery water cooling plate.

[0106] (12) Simulated brazing: The finished composite panels were sampled and placed in a Nabertherm test furnace for simulated brazing. The simulated brazing temperature was 600 °C and the temperature was kept at that temperature for 4 min. The panels were slowly cooled to 350 °C in the furnace and then air-cooled to room temperature.

[0107] The average grain size of the core material of the composite plate is 75.3μm. According to GB / T 16865-2023 "Test specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products", the longitudinal tensile strength of the high-strength corrosion-resistant brazing plate for the power battery water-cooling plate prepared in this application is 164.0MPa, the yield strength is 66.0MPa, and the elongation after fracture is 26.2%. The tensile strength of the composite plate after brazing is 158.7MPa, and the yield strength is 60.2MPa. According to the GB / T7998-2023 standard, the brazed composite plate is subjected to an immersion corrosion test, and the corrosion depth of the plate is 70μm after 50 days of immersion.

[0108] Comparative Example 1

[0109] The mass percentage of the core material components are as follows: Si: 0.6%, Fe: 0.4%, Cu: 0.1%, Mn: 1.4%, Zn: 0.04%, Ti: 0.14%, the individual content of the impurity elements is less than 0.05%, the total amount is less than 0.15%, and the balance is Al.

[0110] (1) Melting and Casting: Raw materials are weighed according to the above-mentioned components and added into a melting furnace for melting. After melting, electromagnetic stirring, slag removal, degassing, refining, and semi-continuous casting, a core material layer alloy ingot is obtained; the brazing layer alloy ingot is a 4045 alloy ingot with a specification of 440 mm × 1600 mm × 4900 mm, and the core material layer alloy ingot has a specification of 440 mm × 1700 mm × 4900 mm.

[0111] (2) Homogenization treatment: After the core alloy is cast, the ingot is heated to 600°C and kept warm for 18 hours for homogenization annealing to reduce and eliminate intracrystalline segregation.

[0112] (3) Ingot processing: The brazing layer ingot and the core material layer ingot are milled according to the specification requirements. The milling depth of the upper and lower surfaces is 10 mm, and the milling depth of the small surfaces on both sides is 5 mm. The head and tail parts of the ingot are cut off.

[0113] (4) Preparation of brazing layer: The brazing layer alloy ingot was placed in a heating furnace and preheated to 500°C for 2 h. It was then hot rolled into a slab with a thickness of 40 mm and then sawn into 40×1600×4000 mm.

[0114] (5) Material cladding: The brazing layer blank plate is stacked on the core material layer alloy ingot, and holes are punched at the four corners of the brazing layer blank plate and the core material layer alloy ingot in a direction perpendicular to the plate surface and riveted.

[0115] (6) Preheating before rolling: The mechanically compounded alloy ingot is preheated to 490°C and kept warm for 2 hours.

[0116] (7) Hot rolling: The preheated composite ingot is hot rolled at a starting rolling temperature of 470°C and a final rolling temperature of 320°C, and rolled into a 4.0 mm composite hot rolled coil in multiple passes.

[0117] (8) Cold rolling: The composite hot rolled coil is rolled into a 1.5 mm composite cold rolled coil through three passes, and the final rolling processing rate is 25%.

[0118] (9) Finished product annealing: The composite cold-rolled coil is subjected to finished product annealing at a temperature of 400°C for 2 hours.

[0119] (10) Finishing: The finished annealed coil is straightened and shaped on a stretch-bend straightening machine to obtain a finished aluminum alloy composite sheet.

[0120] (11) Shearing: The finished aluminum alloy composite sheet is sheared and formed to obtain a high-strength and corrosion-resistant aluminum alloy finished sheet for a power battery water cooling plate.

[0121] (12) Simulated brazing: The finished composite panels were sampled and placed in a Nabertherm test furnace for simulated brazing. The simulated brazing temperature was 590 °C and the temperature was kept at that temperature for 6 min. The panels were slowly cooled to 350 °C in the furnace and then air-cooled to room temperature.

[0122] The average grain size of the core material of the composite plate is 80.1μm. According to GB / T 16865-2023 "Test specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products", the longitudinal tensile strength of the high-strength corrosion-resistant aluminum alloy plate for the water-cooling plate of the power battery prepared in this application is 155.6MPa, the yield strength is 60.3MPa, and the elongation after fracture is 22%. The tensile strength of the composite plate after brazing is 150.4MPa and the yield strength is 55.5MPa. According to the GB / T7998-2023 standard, the brazed composite plate is subjected to an immersion corrosion test, and the corrosion depth of the plate after 50 days of immersion is 125μm.

[0123] Comparative Example 2

[0124] The mass percentage of the core material components are as follows: Si: 0.6%, Fe: 0.5%, Cu: 0.15%, Mn: 1.3%, Zn: 0.05%, Ti: 0.15%, the individual content of the impurity elements is less than 0.05%, the total amount is less than 0.15%, and the balance is Al.

[0125] (1) Melting and Casting: Raw materials are weighed according to the above-mentioned components and added into a melting furnace for melting. After melting, electromagnetic stirring, slag removal, degassing, refining, and semi-continuous casting, a core material layer alloy ingot is obtained; the brazing layer alloy ingot is a 4045 alloy ingot with a specification of 440 mm × 1600 mm × 4900 mm, and the core material layer alloy ingot has a specification of 440 mm × 1700 mm × 4900 mm.

[0126] (2) Homogenization treatment: After the core alloy is cast, the ingot is heated to 610°C and kept warm for 18 hours for homogenization annealing to reduce and eliminate intracrystalline segregation.

[0127] (3) Ingot processing: The brazing layer ingot and the core material layer ingot are milled according to the specification requirements. The milling depth of the upper and lower surfaces is 10 mm, and the milling depth of the small surfaces on both sides is 5 mm. The head and tail parts of the ingot are cut off.

[0128] (4) Preparation of brazing layer: The brazing layer alloy ingot was placed in a heating furnace and preheated to 500°C for 2 h. It was then hot rolled into a slab with a thickness of 40 mm and then sawn into 40×1600×4000 mm.

[0129] (5) Material cladding: The brazing layer blank plate is stacked on the core material layer alloy ingot, and holes are punched at the four corners of the brazing layer blank plate and the core material layer alloy ingot in a direction perpendicular to the plate surface and riveted.

[0130] (6) Preheating before rolling: The ingot after mechanical compounding is preheated to 500°C and kept warm for 2h.

[0131] (7) Hot rolling: The preheated composite ingot is hot rolled at a starting rolling temperature of 480°C and a final rolling temperature of 320°C, and rolled into a 4.0 mm composite hot rolled coil in multiple passes.

[0132] (8) Cold rolling: The composite hot rolled coil is rolled into a 2.0 mm composite cold rolled coil through three passes, and the final rolling processing rate is 29%.

[0133] (9) Finished product annealing: The composite cold-rolled coil is subjected to finished product annealing at a temperature of 380°C for 2 hours.

[0134] (10) Finishing: The finished annealed coil is straightened and shaped on a stretch-bend straightening machine to obtain a finished aluminum alloy composite sheet.

[0135] (11) Shearing: The finished aluminum alloy composite sheet is sheared and formed to obtain a high-strength and corrosion-resistant aluminum alloy finished sheet for a power battery water cooling plate.

[0136] (12) Simulated brazing: The finished composite panels were sampled and placed into a Nabertherm test furnace for simulated brazing. The simulated brazing temperature was 600 °C and the temperature was kept at that temperature for 4 min. The panels were slowly cooled to 350 °C in the furnace and then air-cooled to room temperature.

[0137] The average grain size of the core material of the composite plate is 81.2μm. According to GB / T 16865-2023 "Test specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products", the longitudinal tensile strength of the high-strength corrosion-resistant aluminum alloy plate for the water-cooling plate of the power battery prepared in this application is 155.0MPa, the yield strength is 61.0MPa, and the elongation after fracture is 22.5%. The tensile strength of the composite plate after brazing is 149.2MPa, and the yield strength is 54.8MPa. According to the GB / T7998-2023 standard, the brazed composite plate is subjected to an immersion corrosion test, and the corrosion depth of the plate after 50 days of immersion is 120μm.

Claims

1. A high-strength, corrosion-resistant aluminum alloy brazing sheet for a power battery water-cooling plate, characterized in that: The brazing sheet is formed by rolling and compounding a brazing layer and a core material layer. The core material layer aluminum alloy consists of 0.4% to 1.0% Si, 0.2% to 0.7% Fe, 0.2% to 1.1% Cu, 1.2% to 1.8% Mn, Zn≤0.05%, Ti of 0.05% to 0.2%, and the balance of Al in terms of mass percentage. The brazing layer is 4045 aluminum alloy.

2. The method for preparing a high-strength and corrosion-resistant aluminum alloy brazing sheet material for a power battery water-cooling plate according to claim 1, characterized in that: The method proceeds as follows:

1. Weigh 0.4% to 1.0% Si, 0.2% to 0.7% Fe, 0.2% to 1.1% Cu, 1.2% to 1.8% Mn, Zn≤0.05%, Ti is 0.05% to 0.2%, and the balance is Al according to the mass percentage to obtain the raw material of the core material layer; then perform semi-continuous casting to obtain the alloy ingot of the core material layer; 2. heating the core alloy ingot to 600°C to 630°C and keeping it at that temperature for 16h to 24h to perform homogenization annealing treatment on the ingot; 3. Milling the brazing layer 4045 alloy ingot and the core material layer alloy ingot processed in step 2; 4. hot rolling and sawing the preheated brazing layer alloy ingot; 5. stacking the hot-rolled brazing layer alloy ingot on the core material layer alloy ingot, and punching holes in the direction perpendicular to the plate surface at the four corners of the brazing layer blank plate and the core material layer alloy ingot and riveting them together to obtain a composite alloy ingot; 6. Preheating the composite alloy ingot, and then hot rolling it to form a composite hot-rolled coil; rolling the composite hot-rolled coil again to form a composite cold-rolled coil, and annealing it to obtain an annealed coil; 7. The annealed coil is straightened, shaped and sheared on a stretch-bending straightening machine to obtain a high-strength, corrosion-resistant aluminum alloy brazing sheet for a power battery water-cooling plate.

3. The method for preparing a high-strength and corrosion-resistant aluminum alloy brazing sheet material for a power battery water-cooling plate according to claim 2, characterized in that: The thickness of the brazing layer alloy ingot is 5% to 10% of the thickness of the composite alloy ingot.

4. The method for preparing a high-strength and corrosion-resistant aluminum alloy brazing sheet material for a power battery water-cooling plate according to claim 2, characterized in that: The milling depth of step three is: the milling depth of the upper and lower surfaces is 5mm to 15mm, and the milling depth of the small surfaces on both sides is 2mm to 10mm.

5. The method for preparing a high-strength and corrosion-resistant aluminum alloy brazing sheet material for a power battery water-cooling plate according to claim 2, characterized in that: Step 4: Place the brazing layer alloy ingot in a heating furnace and preheat it to 480°C to 520°C for 2h to 6h to obtain the preheated brazing layer alloy ingot.

6. The method for preparing a high-strength and corrosion-resistant aluminum alloy brazing sheet material for a power battery water-cooling plate according to claim 2, characterized in that: Step 6: Preheat the composite ingot to 460°C to 500°C and keep it warm for 2h to 4h.

7. The method for preparing a high-strength and corrosion-resistant aluminum alloy brazing sheet material for a power battery water-cooling plate according to claim 2, characterized in that: Step 6: The starting rolling temperature of hot rolling is 420°C to 480°C, and the final rolling temperature is 300°C to 360°C.

8. The method for preparing a high-strength and corrosion-resistant aluminum alloy brazing sheet material for a power battery water-cooling plate according to claim 2, characterized in that: Step 6: The thickness of the composite hot-rolled material coil is 3.0 mm to 5.0 mm.

9. The method for preparing a high-strength and corrosion-resistant aluminum alloy brazing sheet material for a power battery water-cooling plate according to claim 2, characterized in that: The reduction rate of the final rolling pass of the composite cold rolled coil is 20% to 40%, and the finished product thickness is 1.0 mm to 2.0 mm.

10. The method for preparing a high-strength and corrosion-resistant aluminum alloy brazing sheet material for a power battery water-cooling plate according to claim 2, characterized in that: Step six: annealing temperature is 340°C to 440°C, and the temperature is kept for 1h to 3h.

Citation Information

Patent Citations

  • Aluminum alloy brazing sheet and manufacturing method thereof as well radiator part

    CN102554585A

  • Brazing aluminum alloy composite board used for heat exchanger, core layer material and preparation method

    CN106827712A

  • Aluminum alloy high-strength water cooling plate for new energy power battery and preparation method of aluminum alloy high-strength water cooling plate

    CN114606403A

  • Preparation method and application of high-strength O-state single-sided brazing sheet

    CN117568666A

  • Method of producing brazing sheet excellent in strength and solder erosion resistance

    JP2005177826A

Cited By

  • High-strength and high-corrosion-resistance aluminum alloy composite board as well as preparation method and application thereof

    CN121733881A